2006
DOI: 10.1111/j.1743-6109.2006.00102.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo delivery of heat shock protein 70 accelerates wound healing by up‐regulating macrophage‐mediated phagocytosis

Abstract: Injury causes tissue breakdown, which releases large quantities of intracellular contents into the extracellular space. Some of these materials are well-established activators of the immune system and include heat shock proteins (HSPs), uric acid, nucleotides, High Mobility Group Box-1 protein (HMGB-1), and DNA. Here, we show that in vivo delivery of HSPs into BALB/cJ mice with full-thickness wounds accelerates the rate of wound closure by 60% as compared with control-treated mice. The onset is rapid and the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
82
0
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 59 publications
2
82
0
7
Order By: Relevance
“…Increasing the recruitment of monocytes or macrophages accelerates wound healing (22,60). Inhibition of macrophage phagocytosis with antimacrophage serum also slows wound healing (31), whereas administration of heat shock protein 70, which stimulates macrophage phagocytosis (60), accelerates wound healing (29). These reports suggest that macrophage phagocytosis is essential for normal wound healing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing the recruitment of monocytes or macrophages accelerates wound healing (22,60). Inhibition of macrophage phagocytosis with antimacrophage serum also slows wound healing (31), whereas administration of heat shock protein 70, which stimulates macrophage phagocytosis (60), accelerates wound healing (29). These reports suggest that macrophage phagocytosis is essential for normal wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Leibovich and Ross (31) reported that elimination of local macrophages at the wound site impairs the wound-healing process, and impaired macrophage phagocytic function also leads to a defect in wound healing (54). Furthermore, macrophages might be activated at the wound site, where a large amount of the intracellular content is released into the extracellular space (29), and these macrophages produce cytokines, growth factors, and chemokines, which promote further recruitment of immune cells (7,41). These tissue macrophages may play important roles in wound healing immediately after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are a part of the chaperone group that is expressed intracellularly under normal conditions. Expression levels are increased during heat shock (2,3) and by other types of stress, such as infection, inflammation, recovery from anoxia, and glucose starvation (3). As cytoprotective chaperones, Hsps act in the conformational change of other proteins, the formation of protein multicomplexes, thermotolerance, and the prevention of protein aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…Hsp expression is increased during the normal reparative process and diminished during the chronic reparative process (2,3). Hypotheses regarding marked expression of Hsp during normal repair highlight the fact that, during healing, cells are exposed to a sequence of injuries, such as dehydration, alterations in the partial pressure of the oxygen and carbon dioxide, transient ischemia, and high production of reactive oxygen metabolites (5).…”
Section: Introductionmentioning
confidence: 99%